1992
DOI: 10.1073/pnas.89.22.10787
|View full text |Cite
|
Sign up to set email alerts
|

Identification and selective inhibition of an isozyme of steroid 5 alpha-reductase in human scalp.

Abstract: Steroid Sa-reductase (EC 1.3.1.22) catalyzes the reduction of testosterone to dihydrotestosterone. The Sareductase found in human scalp has been compared with the enzyme found in prostate. The scalp reductase has a broad pH optimum centered at pH 7.0. This is distinctiy different from the pH optimum of 5.5 observed with the prostatic form of the enzyme. These enzymes also differ in the K.. for testosterone, which is 25-fold higher for the scalp reductase. The most significant difference between the two enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 31 publications
2
56
1
Order By: Relevance
“…They are called 5a-R type 1 and 2 (5a-R1 and 5a-R2). Studies using specific inhibitors of 5a-R1 and 5a-R2 (finasteride) showed that 5a-R2 enzymatic activity is predominant in the urogenital sinus and in genital skin, whereas 5a-R1 is predominant in the central nervous system (only type 1), in pubic skin, in the adult scalp and in the nonsex skin of the normal male, normal women and hirsute patients (14)(15)(16)(17). However, the distribution and role of 5a-R1 is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…They are called 5a-R type 1 and 2 (5a-R1 and 5a-R2). Studies using specific inhibitors of 5a-R1 and 5a-R2 (finasteride) showed that 5a-R2 enzymatic activity is predominant in the urogenital sinus and in genital skin, whereas 5a-R1 is predominant in the central nervous system (only type 1), in pubic skin, in the adult scalp and in the nonsex skin of the normal male, normal women and hirsute patients (14)(15)(16)(17). However, the distribution and role of 5a-R1 is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The boundaries of these narrow regions are listed in Table 1. Of the four genes in single gene regions, Catenin Delta-2 (CTNND2) has been shown to be overexpressed in prostate cancer (Burger et al, 2002) and Steroid 5-Alpha-Reductase (SRD5A1), which catalyses the conversion of testosterone into the more potent androgen dihydrotestosterone (Harris et al, 1992), has been shown to be overexpressed in breast cancer (Wiebe and Lewis, 2003). The Triple Functional Domain gene (TRIO) in Region A4 ( Figure 1c) and the Glial Cell Line-Derived Neurotrophic Factor gene (GDNF) in Region A6 (Figure 1d), however, have not been directly implicated in cancer and were further investigated in this study (see below).…”
Section: Novel Amplifications Defined In Cis Lesionsmentioning
confidence: 99%
“…Studies of molecular cloning have characterized two genes that encode the type 1 and type 2 5α-reductase isoenzymes (13,14). The 5α-reductase isoenzyme predominant in the skin is type 1 (SDR5A1) (15), which has 60% homology with 5α-reductase type 2 (SDR5A2) that is characteristic of the prostate gland (14). An increase in 5α-reductase activity was demonstrated in genital and pubic skin fibroblasts from hirsute patients in comparison to the skin of normal women (8,16).…”
Section: Introductionmentioning
confidence: 99%